A psychoacoustical approach to resolving office noise distraction. Issue 4 (12th November 2018) - Oseland, Nigel; Hodsman, Paige
Abstract : Purpose: The purpose of this paper is to determine whether noise is affected by psychological factors rather than simply by physical metrics. For example, personality type, age, perceived control and screening ability were explored, as well as the choice of primary workplace. Design/methodology/approach: An online survey was conducted which resulted in 517 valid responses. The survey included the personality profiling along with questions related to noise and personal circumstances. The key noise metrics were perceived performance, ability to work, well-being and stress plus three noise indices: concentration, distraction and speech interference. Findings: The survey revealed that personality type does affect noise perception, in particular extroversion and neuroticism. Perceived control, screening ability, age, workplace, design and focused work are also factors. Personal variables accounted for 25 per cent of the variance in the ability to carry out work, and for 40 per cent of the variance in concentration and speech interference. Research limitations/implications: Whilst statistically significant differences were found for most of the psychological and personal variables, the size of effect was smaller than anticipated. This is likely because the survey was carried out across a range or workplaces, rather than in a laboratory, with a number of uncontrolled extraneous factors. Practical implications: The research has resulted in the development of a design guidance document for controlling noise distractions based on more psychoacoustic, people-centred, principles than purely physical ones. Originality value: Most acoustics research is conducted in the laboratory and focuses on the physical sound properties. This research took a psychoacoustic approach focusing more on psychological and personal factors, and was carried out in the real world.